The Rise of Intelligent Finance : A SPAR-4-SLR Approach in Exploring the Role of AI in Enhancing Financial Planning and Financial Literacy - Gupta, Lovleen; Kumar, Santosh (Indian Journal of Research in Capital Markets, 2025)
Purpose : In this study, we presented a systematic literature review of how artificial intelligence (AI) and financial technology (FinTech) have converged with the concept of financial literacy, financial inclusion, and its planning. Methodology : A total of 879 papers were extracted from the Scopus database for the period 2010 to 2025, and after refinement using SPAR-4-SLR, we identified 54 articles. To have a clear understanding and to trace the intellectual development of the literature in this area, we applied the ADO-TCM framework. Findings : There is a clear progression of trends in this domain. Earlier studies were based on basic theories, and subsequent work has applied models such as TAM, UTAUT, and the diffusion of innovation to capture technology acceptance. A significant portion of the literature is inclined toward institutional and systemic perspectives, including agency theory, human capital, and risk management. Despite this theoretical richness, methodologies remain limited, with survey and experimental studies dominating, while longitudinal, comparative, and mixed-method approaches are scarce. Practical Implication : It has been noted that there is a deficiency of literature in the developing economies, which shows a major gap in the literature, and more critical consideration is required. A broader theoretical integration, methodological diversification, and greater attention to the underrepresented context are required for strengthening the future of AI-driven financial literacy research. Originality : This research provided a new dimension to look at the literature development in this area. Additionally, the model which is used in this paper is most suitable to give a rigorous view of every element and variable used in the literature.